Quality model for web services from multi-stakeholders' perspective - Balfagih, Z.; Hassan, M.F. (2009)
In the current implementation of SOA using web services, where different services can provide the same functionality for consumers, QoSs of these services are essential in determining the most suitable services for consumers. Although QoS for web services has attracted wide attention in the literature for the past few years, most of the current efforts did not consider the multi-stakeholders nature of web services. Unlike traditional software paradigms, SOA applications owned, developed, and/or used by different stakeholders. Those stakeholders are provider, consumer, developer, and broker. As a result, non-functional requirements are different from one stakeholder to another.This paper presents a quality model that classifies nonfunctional characteristics based on the different stakeholders' requirements. In the discussion of the stakeholders we focus on developer, provider, and consumer. The model presents also some metrics for these characteristics. We argue that this model gives better view for SOA and web services quality requirements from different perspectives.